Love, trust and commitment in preserving long-distance marital relationships - Joki Perdani Sawai; Rezki Perdani Sawai; Mahirah Masdin (Fakulti Psikologi dan Pendidikan, 2021)
A study was conducted to investigate the role of love, trust, and commitment in preserving long-distance relationships among married couples. The long-distance relationship factor focused on the extent to which the three sentiments determine the preservation of marriages. The study was conducted on 110 long-distance married couples. The three domains of love measured were intimacy, passion, and commitment. Trust was measured using a single domain while the commitment domains involved the intention to persist, attachment and long-term orientation. The love variable was measured using the Triangular Love Scale, trust was measured using the Dyadic Trust Scale, and commitment was based on the Investment Model Scale (IMS) (Rusbult, Martz, & Agnew, 1998), while marital maintenance was measured using the Relationship Maintenance Scale. The study found that passion (r = .294 **, k <.002) had a significant positive relationship with marital maintenance while trust (r = .249 **, k <.001) showed a similar relationship. Further, only the commitment domain for long-term orientation (r = .199*, k <.002) showed a significant positive relationship with marital maintenance. Thus, the results indicate that passion, trust and long-term commitment orientation are likely to enhance marital preservation among long-distance married couples. The implications are that passion, trust, and long-term commitment orientation are crucial to protect and strengthen long-distance marriage bonds among such couples.